Performance Comparison of Monocrystalline PV Module Using Floating and Non-Floating Method - Mohamad Ilas, Mohamad Azri; Islam, Syed Zahurul (Evolution in Electrical and Electronic Engineering, 2021)
This project explains the concept of comparative performance of monocrystalline PV modules in grasslands and floating lakes, where the performance efficiency of the two types of methods installed are being analyzed. The main objectives of this paper are to design a floating lake PV system to float on the water surface, to develop an algorithm that can automatically agitate a proper reading of the parameter required, and to design a prototype for the development of the floating lake PV system where the water is used as natural cooling effects. In this project, Arduino UNO is selected to program the system as a microcontroller, while sensors such as a voltage sensor, a current sensor, and a temperature sensor are used to initiate data reading for system data logger 1 and system data logger 2. The system has been built accordingly and the performance of the system is tested. The result shows that the system can run with the aid of solar energy and the overall concept of the system can be implemented for the real application system.